Research on Dynamic Stability Optimization of Rock Spreader considering Prevention of Geological Subsidence and Local Collapse in Reclamation Area - Baofu Kou; Pengliang Huo; Xin Shi (Advances in Civil Engineering)
The uneven stacking of waste rock materials caused by the dynamic instability of rock spreaders cannot be ignored for geological subsidence and local collapse in reclamation areas. Based on the dynamic stability of the existing rock spreader, combined with the actual application conditions, the load conditions of the rock spreader are analyzed. The static and dynamic analysis and optimization of the key structures such as the receiving arm, the discharging arm, and the main tower are carried out by using the topology optimization method. The optimized virtual prototype of the whole machine is established to verify its rationality. The research results show that the total weight of key parts such as receiving boom, discharging boom, and the main tower is reduced by about 4.5% (4650 kg), the lower-order vibration frequencies below the fifth order of those parts are not within the resonance range, and the stability of the whole machine is greatly improved, which fundamentally solves the problem of uneven rock stacking caused by impact stability. And, the maximum stress and deflection of the whole machine under the worst working conditions meet the actual requirements. The research ideas and conclusions can provide solutions to prevent the subsidence or local collapse of reclamation areas caused by uneven stacking materials.